CXCR4 Inhibition Counteracts Immunosuppressive Properties of Metastatic NSCLC Stem Cells - Fortunato, Orazio; Belisario, Dimas Carolina; Compagno, Mara; Giovinazzo, Francesca; Bracci, Cristiano; Pastorino, Ugo; Horenstein, Alberto; Malavasi, Fabio; Ferracini, Riccardo; Scala, Stefania; Sozzi, Gabriella; Roz, Luca; et al. (Frontiers in Immunology, 2020)
Cancer stem cells (CSCs) are functionally defined as the cell subset with greater potential to initiate and propagate tumors. Within the heterogeneous population of lung CSCs, we previously identified highly disseminating CD133+CXCR4+ cells able to initiate distant metastasis (metastasis initiating cells-MICs) and to resist conventional chemotherapy. The establishment of an immunosuppressive microenvironment by tumor cells is crucial to sustain and foster metastasis formation and CSCs deeply interfere with immune responses against tumors. How lung MICs can elude and educate immune cells surveillance to efficiently complete the metastasis cascade is however currently unknown. We show here in primary tumors from non-small cell lung cancer (NSCLC) patients that MICs express higher levels of immunoregulatory molecules compared to tumor bulk, namely PD-L1 and CD73, an ectoenzyme that catalyzes the production of immunosuppressive adenosine, suggesting an enhanced ability of MICs to escape immune responses. To investigate in vitro the immunosuppressive ability of MICs, we derived lung spheroids from cultures of adherent lung cancer cell lines, showing enrichment in CD133+CXCR4+MICs, and increased expression of CD73 and CD38, an enzyme that also concurs in adenosine production. MICs-enriched spheroids release high levels of adenosine and express the immunosuppressive cytokine IL-10, that is undetectable in adherent cell counterpart. To prevent dissemination of MICs, we tested peptide R, a novel CXCR4 inhibitor that effectively controls in vitro lung tumor cells migration/invasion. Notably, we observed a decreased expression of CD73, CD38 and IL-10 following CXCR4 inhibition. We also functionally proved that conditioned medium from MICs-enriched spheroids compared to adherent cells has an enhanced ability to suppress CD8+ T cell activity, increase Treg population and induce the polarization of tumor-associated macrophages (TAMs), which participate in suppression of T cells. Treatment of spheroids with anti-CXCR4 rescued T cell cytotoxic activity and prevented TAM polarization, likely by causing the decrease of adenosine and IL-10 production. Overall, we provide evidence that the subset of lung MICs shows high potential to escape immune control and that inhibition of CXCR4 can impair both MICs dissemination and their immunosuppressive activity, therefore potentially providing a novel therapeutic target in combination therapies to improve efficacy of NSCLC treatments.